Estudio de factibilidad para la creación de una microempresa dedicada a la elaboración y comercialización de floreros de botellas recicladas en el cantón Piñas, de la provincia de El Oro - Mora Rojas, Fabiola Alexandra (2016)
The overall objective of this thesis is "determine a project's feasibility studies for the creation of a small company dedicated to the production and marketing of vases of bottles recycled in the Canton pineapples, in the province of gold", the work was developed with the use of library materials of office and technological methods of research as the inductive, deductive analytical and statistical we apply the same technique of observation and survey, the latter was performed on a sample of 378 families living in the Canton pineapples and 23 locations that sell similar products. The market study, found an effective demand of vases of 24.457 units, and an offer of 328 vases, by the total there is an unsatisfied 24.122 drives demand The technical study was determined the installed capacity of 7,800 vases from recycled bottles produced annually and meet the demand unsatisfied 24.122 with the 32.34% segmentation and capacity used 5.460 with 70% increasing by 3% each year to cover 95% of installed capacity. Micro will operate the piñas canton, located in Calle Loja and Gonzales Suarez. This place was chosen because it meets all the requirements necessary for its operation. The organizational study was declared the need to recruit personnel with capabilities to fulfill different roles according to the requirement profile. Legally the company shall be constituted as a limited liability company called "Fabys designs and creations Ltda. his business making vases from recycled bottles with a projection of 10 years." The financial study will have an investment of 8.615.10, providing an equity of 615.10 dollars which is the 7.14% and 8.00.00 dollars which is the 92.86. % financed by the Banco del Pichincha with a 15% annual interest rate. In the State of losses and profits is announced for the first year there is a benefit of 3.155.80 and a cash flow of 3.102.41 reaching a 15.430.83 utility for the last year of the project. The point of equilibrium occurs when the company is working at a capacity of 79.47% and has sales of 46.341.79 dollars. At this point in the company or win or lose With regards to the financial valuation have feasible results means that we can develop the project for the creation of micro-enterprises through the main indicators that are net present value of 30.557.58 which is better than positive one this ensures the profitability of the project, rate internal return 60.27%, recovery period of capital in 2 years 2 months and 12 days with a cost benefit of 1.21 cents; The analysis of sensitivity with an increase of 9.81% and a decrease in income from 7.99%. Therefore, the study is favorable. In addition conclusions and recommendations were determined by what is considered the project is profitable which generates jobs for commercial development within the Piñas Canton in the province of El Oro